2017
DOI: 10.1111/jace.15059
|View full text |Cite
|
Sign up to set email alerts
|

Mixed modifier effect in lithium‐calcium borosilicate glasses

Abstract: The mixed modifier effect (MME) in the lithium‐calcium borosilicate glasses, which have a composition of 0.4[(1−x)Li2O–xCaO]–0.6[(1−y)B2O3–ySiO2] with x in the range of 0~1 and y in the range of 0.33~0.83, is investigated. The MME manifests itself as a positive deviation from linearity in the activation energy of electrical conductivity (Eaσ) and as a negative deviation from linearity in the fraction of four‐coordinated boron (N4), glass transition temperature (Tg), dilatometric softening temperature (Td), Vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(93 reference statements)
4
8
0
Order By: Relevance
“…However, the hardness was found to be higher for the NL series compared to the NK series. Nevertheless, the values are in close agreement with other alkali silicate glass compositions 51,61 and higher than alkali borates. 62 The glass transition temperature (T g ) obtained from the differential thermal analyzer was found to increase for the NL series while it decreased for the NK series ( Figure 5E).…”
Section: Glasses With Mixed-alkali Ionssupporting
confidence: 87%
See 2 more Smart Citations
“…However, the hardness was found to be higher for the NL series compared to the NK series. Nevertheless, the values are in close agreement with other alkali silicate glass compositions 51,61 and higher than alkali borates. 62 The glass transition temperature (T g ) obtained from the differential thermal analyzer was found to increase for the NL series while it decreased for the NK series ( Figure 5E).…”
Section: Glasses With Mixed-alkali Ionssupporting
confidence: 87%
“…The dilatometric results of the present glasses revealed a coefficient of thermal expansion (CTE) in the range 8-10 ppm/K ( Figure 5F) which lies well in the expected range of alkali silicate glasses. 51,63 More importantly, it is in close agreement with CTE of the commercially available soda lime glass as desired for CIGS/ CZTS-based solar cell substrates, 64 ruling out the possibility of device failure due to thermal mismatch between substrate and thin film. It may be noted that the absorber layers (ie, CIGS or CZTS) routinely require postdeposition annealing at temperatures ~500°C for crystallization and densification.…”
Section: Glasses With Mixed-alkali Ionssupporting
confidence: 54%
See 1 more Smart Citation
“…It has been shown that borosilicate glass T g is affected by many compositional parameters such as: (a) the R and K values defined as the ratio Na 2 O/B 2 O 3 and SiO 2 /B 2 O 3 , respectively 19,20 ; (b) the presence of Al 2 O 3 21,22 ; and (c) the nature of the network-modifying cation. [23][24][25] Regardless of the major element chemical composition (ie, silicate or borosilicate glasses), it has been demonstrated that the presence of volatile species influences T g . For instance, H 2 O provokes a dramatic decrease in T g, [26][27][28][29] whereas CO 2 only weakly decreases T g .…”
Section: Introductionmentioning
confidence: 99%
“…For the particular case of borosilicate glasses, there has been extensive work in determining the change in T g as a function of several key composition parameters. It has been shown that borosilicate glass T g is affected by many compositional parameters such as: (a) the R and K values defined as the ratio Na 2 O/B 2 O 3 and SiO 2 /B 2 O 3 , respectively 19,20 ; (b) the presence of Al 2 O 3 21,22 ; and (c) the nature of the network‐modifying cation 23‐25 …”
Section: Introductionmentioning
confidence: 99%